Histologic evaluation of bone healing capacity following application of inorganic bovine bone and a new allograft material in rabbit calvaria. - Mojgan Paknejad; AmirReza Rokn; Nina Rouzmeh; Mohadeseh Heidari; Azadehzeinab Titidej; Mohammad Javad Kharazifard; Ali Mehrfard (Tehran University of Medical Sciences, 2015)
Considering the importance of bone augmentation prior to implant placement in order to obtain adequate bone quality and quantity, many studies have been conducted to evaluate different techniques and materials regarding new bone formation. In this study, we investigated the bone healing capacity of two different materials deproteinized bovine bone mineral (DBBM with the trade name of Bio-Oss) and demineralized freeze-dried bone allograft (DFDBA with the trade name of DynaGraft).This randomized blinded prospective study was conducted on twelve New Zealand white rabbits. Three cranial defects with an equal diameter were created on their calvarium. Subsequently, they were distributed into three groups: 1. The control group without any treatment; 2. The Bio-Oss group; 3. The DynaGraft group. After 30 days, the animals were sacrificed for histologic and histomorphometric analysis.Substantial new bone formation was observed in both groups. DynaGraft: 56/1 % ± 15/1 and Bio-Oss: 53/55 % ± 13/5 compared to the control group: 28/6 % ± 11/2. All groups showed slight inflammation and a small amount of residual biomaterial was observed.Considerable new bone formation was demonstrated in both DynaGraft and Bio-Oss groups in comparison with the control group. Both materials are considered biocompatible regarding the negligible foreign body reaction.